Penerapan Keselamatan dan Kesehatan Kerja Dalam Pencegahan Wabah Covid-19 di PT. Rosaria Bakery - Muhammad Nabil Riyanto; Sukanta Sukanta; Jauhari Arifin (Peneliti.net, 2022)
Research has made efforts to contain the spread of the Covid-19 virus in the work area of ​​PT. Rosaria Bakery. This study aims to determine how occupational safety and health programs are implemented in an effort to prevent the spread of the covid-19 virus in the work environment of PT. Rosaria Bakery has formed a Covid-19 Team which has established Working Guidelines for the New Normal Conditions. This work guide contains several modules that must be adhered to by all employees and other related parties to PT. Rosaria Bakery, including the Work From Home module, the driving module, the receiving guests and packages module, the meeting module, the dining module (canteen), the prayer prayer module, the janitor module and the Work Guide. The purporse of this study is to monitor the implementation of occupational safety and health programs carried out by workers in an affort to protect all employees. And this method han an employee as a resource person who is working some where by isong validation and reliability test.